Tumor budding is a valuable prognostic parameter in endometrial carcinomas - Irfan Ocal; Ismail Guzelis (Wolters Kluwer Medknow Publications, 2022)
Background: Tumor budding (TB) is a morphological finding believed to play an important role in determining the prognosis in many cancers. Aim: Our aim is to evaluate the prognostic importance of TB in endometrial carcinomas. Settings and Design: Two-hundred-eleven endometrial cancers were obtained from 2008 to 2015 that were comprised of those having undergone surgical staging with a hysterectomy and at least 5 years followed up. Material and Methods: All hematoxylin and eosin stained slides were reevaluated for the status of TB. Statistical Analysis: Nonparametric tests, the Kaplan-Meier method, the Log-rank test, and Cox proportional hazard regression were used. Results and Conclusion: TB was found to correlated with larger diameter (P = 0.000), nonendometrioid (P = 0.038), mixed cell types (P = 0.005), higher grade (P = 0.000), deeper invasion of the myometrium (P = 0.000), cervical stromal invasion (P = 0.000), advanced pT (P = 0.011), lymph node involvement (P = 0.000), lymphovascular invasion (P = 0.000), and advanced stage (P = 0.000). The presence of TB worsens the 5-year overall survival (OS) (P = 0.0001). In cases such as grade 1, pT1, or stage 1 endometrial carcinomas, the presence of TB decreases the OS rate (P = 0.00017, P = 0.0016, P < 0.0001). Our result suggested that the presence of TB adversely affects the prognosis. It was concluded that TB could be a valuable prognostic parameter.